Nyisig: Sebuah Upaya Dokumentasi Tradisi - Nurullita, Hervina; Agustina, Nindi (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
Culture is part of all living things that are always attached to their environment. Culture needs to be preserved so that it does not become extinct. Therefore, maintaining the traditions that exist around us is an obligation for humans. One of the traditions that is still practiced and almost abandoned by a group of people is the tradition of eating betel nut or nyisig. This tradition is carried out by Using women in Jambesari Village, Giri District, Banyuwangi Regency. This research aims to analyze how the existence of the nyisig tradition, what aspects are contained in the nyisig tradition, what materials are needed in the nyisig tradition, why people started to leave this nyisig tradition. This research method is a qualitative method. Data were collected using interviews, documentation and literature study. The result of this research is the documentation of the nyisig tradition that is still practiced by some Using women in Jambesari village.